Urea supplementation improves mRNA in vitro transcription by decreasing both shorter and longer RNA byproducts - Combes Francis; Pettersson Frida J; Bui Thanh-Huong; Molska Alicja; Komissarov Artem; Parot Jérémie; Borgos Sven Even (RNA Biology)
The current letter to the editor describes the presence of RNA byproducts in small-scale in vitro transcription (IVT) reactions as evaluated by capillary gel electrophoresis, asymmetric flow field flow fractionation, immunoblotting, cell-free translation assays, and in IFN reporter cells. We compare standard T7 RNA polymerase (RNAP) based IVT reactions to two recently described protocols employing either urea supplementation or using the VSW3 RNAP. Our results indicate that urea supplementation yields considerably less RNA byproducts and positively affects the overall number of full-length transcripts. In contrast, VSW3 IVT reactions demonstrated a low yield and generated a higher fraction of truncated transcripts. Lastly, both urea mRNA and VSW3 mRNA elicited considerably less IFN responses after transfection in mouse macrophages.